Microscopic Pore Structure Characteristics and Methane Adsorption of Vitrain and Durain. (23rd November 2020) - Yang, Fu; Ma, Dongmin; Duan, Zhonghui; Ren, Dazhong; Tian, Tao; Liu, Dengke
Abstract : During reservoir evaluation, the microscopic pore structure of low-rank coal is mainly characterized in order to study the coalbed methane diffuse and migration mechanisms and control. The low-rank coals are very different in pore type and size, so it is necessary to use various techniques to describe their pore structure. For vitrain and durain of the Coal Member of the Yan'an Formation from Huanglong Coalfield, their chemical composition and microscopic pore structure characteristics were studied, and the factors of influencing the pore size distribution (PSD) were explored. Obviously, vitrain and durain are different in chemical composition. Vitrain has higher moisture content, volatile yield, and vitrinite group content than durain. Vitrain and durain mainly contain vitrinite and inertinite, respectively. The pore structure characteristics (e.g., pore types and PSD) of vitrain and durain were systematically by mercury intrusion porosimetry (MIP), low-temperature nitrogen adsorption, and carbon dioxide (CO2) adsorption. The vitrain and durain samples with a micropore size of <2 nm were mainly tested on their specific surface area (SSA) and pore volume (PV). The results show that microporous vitrain has larger SSA and PV than microporous durain, while mesoporous and macroporous vitrain has smaller SSA and PV than mesoporous and macroporous durain. SSA is very positively correlated with PV. The ash content is negatively correlated with SSA and PV. The ash content influences microporous vitrain more greatly than microporous durain, but mesoporous and macroporous durain more greatly than mesoporous and macroporous vitrain. SSA is positively correlated with the vitrinite content of durain and negatively correlated with the inertinite and exinite contents of durain. However, SSA is negatively correlated with the vitrinite and exinite contents of vitrain and positively correlated with the inertinite content of vitrain. Vitrain has higher methane adsorption capacity, desorption rate, and recovery ratio than durain. There are parameters that are obviously affected by the micropore characteristics.